2017
DOI: 10.1159/000455073
|View full text |Cite
|
Sign up to set email alerts
|

Bell's Palsy: Clinical Analysis of 372 Cases and Review of Related Literature

Abstract: Objective: To analyze some clinical and epidemiologic aspects of Bell's palsy (BP) and to develop relevant correlations between existing data in literature and those obtained in this research. Methods: From January 2012 to December 2014, 372 consecutive patients diagnosed with BP were studied retrospectively. We reviewed the patients' data including gender, age, occupation, clinical manifestations, comorbid disease, and the rate of recurrence. Result: The highest incidence was identified in those between 39 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 8 publications
3
39
1
4
Order By: Relevance
“…Aforementioned three studies also a statistically non-significant effect of high blood glucose on BP and HB grade in the diabetic group compared to the non-diabetic group, supporting our finding. In a review study involving 372 cases; it was found that patients with facial palsy most commonly presented with HB grades III and IV [25]. Similarly, in the present study, our patients presented mostly with HB grades III and IV.…”
Section: Discussionsupporting
confidence: 84%
“…Aforementioned three studies also a statistically non-significant effect of high blood glucose on BP and HB grade in the diabetic group compared to the non-diabetic group, supporting our finding. In a review study involving 372 cases; it was found that patients with facial palsy most commonly presented with HB grades III and IV [25]. Similarly, in the present study, our patients presented mostly with HB grades III and IV.…”
Section: Discussionsupporting
confidence: 84%
“…Mansoura University Hospital, Mansoura University, Mansoura, Egypt. 2 Badr University Hospital, Helwan University, Helwan, Egypt.…”
Section: Fundingmentioning
confidence: 99%
“…Bell's palsy (BP) is mostly idiopathic, but viral infections as herpes simplex virus, varicella-zoster virus, and Epstein-Barr virus are suggested [1].The incidence is 15 to 20 per 100,000. The recurrence rate is about 10% [2].The pathophysiology of Bell's palsy includes compression of facial nerve at the internal auditory meatus, due to the inflammatory edema leading to temporary loss of sensory or motor function, but it could lead to permanent nerve degeneration later [3].…”
Section: Introductionmentioning
confidence: 99%
“…A candidate environmental factor may be acute respiratory infection, possibly by reactivating latent herpes virus infection [3]. However, the findings of other studies investigating seasonal variation of Bell's palsy are heterogeneous [1,[7][8][9][10], and the discrepancies may be due to the geographic and climatic area where the studies were conducted [3]. Limitations of our study include the hospitalbased setting, which may have biased the representativeness of our study population (for example, patients with very mild facial asymmetry may choose not to go to an emergency department).…”
Section: Dear Editormentioning
confidence: 99%